2000
DOI: 10.1006/dbio.1999.9579
|View full text |Cite
|
Sign up to set email alerts
|

Subdivision of the Cardiac Nkx2.5 Expression Domain into Myogenic and Nonmyogenic Compartments

Abstract: Nkx2.5 is expressed in the cardiogenic mesoderm of avian, mouse, and amphibian embryos. To understand how various cardiac fates within this domain are apportioned, we fate mapped the mesodermal XNkx2.5 domain of neural tube stage Xenopus embryos. The lateral portions of the XNkx2.5 expression domain in the neural tube stage embryo (stage 22) form the dorsal mesocardium and roof of the pericardial cavity while the intervening ventral region closes to form the myocardial tube. XNkx2.5 expression is maintained th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 41 publications
0
47
0
Order By: Relevance
“…3B and C). NKX2.5 is critical for vasculogenesis and angiogenesis (27). We also assessed the mRNA levels of an intestinal marker, Cyl18, which is mainly expressed in the presumptive small intestine of embryos at the tailbud stage.…”
Section: Pfc Exposure Alters Tissue-specific Mrna Expression In Vivomentioning
confidence: 99%
“…3B and C). NKX2.5 is critical for vasculogenesis and angiogenesis (27). We also assessed the mRNA levels of an intestinal marker, Cyl18, which is mainly expressed in the presumptive small intestine of embryos at the tailbud stage.…”
Section: Pfc Exposure Alters Tissue-specific Mrna Expression In Vivomentioning
confidence: 99%
“…Inductive cues originate from the anterior primitive endoderm (Sugi and Lough 1994;Schultheiss, Xydas et al 1995;Schultheiss, Burch et al 1997;Schultheiss and Lassar 1997) and lateral regions of the embryo (Schultheiss, Xydas et al 1995;Schultheiss, Burch et al 1997;Schultheiss and Lassar 1997), while cardiogenesis is suppressed in the adjacent mesoderm by factors secreted by the neuronal tube (Climent, Sarasa et al 1995;Schultheiss, Burch et al 1997;Raffin, Leong et al 2000). Members of the TGF-β superfamily (TGF-β, nodal, activin and BMP) and the FGF family are known cardiogenic morphogens that activate cardiac transcription factors ).…”
Section: Parallels Between Cardiogenesis In the Embryo And In The Ebmentioning
confidence: 99%
“…In the embryo it is recognized that cardiogenesis is directed via the coordination of inductive cues from the anterior primitive endoderm (Sugi and Lough 1994;Schultheiss, Xydas et al 1995;Sugi and Lough 1995;Schultheiss, Burch et al 1997;Schultheiss and Lassar 1997) and inhibitory cues originating from neurogenic tissue (Climent, Sarasa et al 1995;Schultheiss, Burch et al 1997;Raffin, Leong et al 2000). Accordingly, methods to drive mesoderm and cardiac induction during hESC differentiation have included co-culturing hESCs with the visceral endoderm-like cell line END-2 (Mummery, Ward-van Oostwaard et al 2003) or the addition of Transforming Growth Factor Beta (TGF-β) family proteins (most commonly activin A and Bone Morphogenetic Protein (BMP)-2 or BMP-4) that are known to be secreted by primitive endoderm (Burridge, Anderson et al 2007;Laflamme, Chen et al 2007).…”
Section: Chapter 2 Control Of Human Embryonic Stem Cell Colony and Agmentioning
confidence: 99%
“…5B), and the neural plate was considerably expanded in some embryos implanted with Wnt-1 or Wnt-3a pellets (data not shown). Therefore, it was unclear whether repression of Nkx-2.5 gene expression by Wnt signals reflected a direct effect on precardiac mesoderm or a secondary effect because of the expansion of the neural plate, which is known to express inhibitors of cardiogenesis (Jacobson 1960;Climent et al 1995;Raffin et al 2000).…”
Section: Ectopic Expression Of Wnts Blocks Cardiogenesis From Precardmentioning
confidence: 99%
“…The neural plate/neural tube has long been known to inhibit cardiogenesis (Jacobson 1960;Climent et al 1995;Raffin et al 2000;Tzahor and Lassar 2001). This laboratory has observed that presumptive head mesoderm from stage 8 embryos, when removed from the adjacent inhibitory influence of neural tube, spontaneously differentiates to heart muscle when cultured with foregut endoderm and the overlying nonneural ectoderm (Tzahor and Lassar 2001).…”
Section: Crescent and Dkk-1 Partially Mimic The Heart Inducing Activimentioning
confidence: 99%